2022
DOI: 10.4018/978-1-7998-9581-7.ch008
|View full text |Cite
|
Sign up to set email alerts
|

Role of University Entrepreneurial Ecosystem and Entrepreneurial Self-Efficacy in Shaping Entrepreneurial Intention

Abstract: This chapter is an attempt to explore the role of the university ecosystem and entrepreneurial self-efficacy in shaping entrepreneurial intention of students of higher education institutions in India. The study is empirical in nature and is based on a survey conducted among the students of a private university in India. The causal research design approach was used to explore the causal relationship among dependent and independent variable. Data was collected through a structured questionnaire, and correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Various research has demonstrated that self-efficacy is a crucial cognitive factor in the field of social entrepreneurship and an essential element in the development of intentions towards social entrepreneurship [54][55][56][57]. According to Wang et al [58], the concept of entrepreneurial self-efficacy plays a crucial role in explaining an individual's active involvement in the decision-making process to establish and manage their own business, rather than adopting a passive role.…”
Section: Entrepreneurial Self-efficacy and Social Entrepreneurial Int...mentioning
confidence: 99%
“…Various research has demonstrated that self-efficacy is a crucial cognitive factor in the field of social entrepreneurship and an essential element in the development of intentions towards social entrepreneurship [54][55][56][57]. According to Wang et al [58], the concept of entrepreneurial self-efficacy plays a crucial role in explaining an individual's active involvement in the decision-making process to establish and manage their own business, rather than adopting a passive role.…”
Section: Entrepreneurial Self-efficacy and Social Entrepreneurial Int...mentioning
confidence: 99%
“…It is well-known that practically all countries' economies face varying economic slowdowns (Akhtar et al, 2022). In addition, the worldwide catastrophe brought on by the COVID-19 epidemic has greatly exasperated the employment situation (Gupta, 2022) and profoundly affected society (Ratten and Jones, 2021b). As reported in the Centre for Monitoring Indian Economy (CMIE) survey, India has a dire unemployment scenario in which 10 million people will be classified as unemployed over the next four years, increasing the number of unemployed people to 220 million by 2022.…”
Section: Introductionmentioning
confidence: 99%